2012
DOI: 10.1002/ps.3350
|View full text |Cite
|
Sign up to set email alerts
|

Insect growth regulators as potential insecticides to control olive fruit fly (Bactrocera oleae Rossi): insect toxicity bioassays and molecular docking approach

Abstract: IGR molecules similar to the RH-5849 molecule, and different from methoxyfenozide and tebufenozide, might have potential in controlling this pest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Additionally, as shown in Figure 5, because the larvae consumed many compound-treated leaves during the first 2 days, they showed various symptoms of toxicity in the subsequent growth and developmental stages, such as blackened and unmolted bodies, malformed pupae, and deformed moths (panels A−C of Figure 5). The above phenomena were similar to those previous reports, 29,30 and the findings indicated that these N-benzoylthioureas of osthole probably interfere with the synthesis of the growth hormone of M. separata, causing abnormalities at three growth stages and eventually leading to the death of M. separata. Aphicidal Activity of Osthole-Derived N-Benzoylthioureas against M. persicae.…”
Section: Data Forsupporting
confidence: 91%
“…Additionally, as shown in Figure 5, because the larvae consumed many compound-treated leaves during the first 2 days, they showed various symptoms of toxicity in the subsequent growth and developmental stages, such as blackened and unmolted bodies, malformed pupae, and deformed moths (panels A−C of Figure 5). The above phenomena were similar to those previous reports, 29,30 and the findings indicated that these N-benzoylthioureas of osthole probably interfere with the synthesis of the growth hormone of M. separata, causing abnormalities at three growth stages and eventually leading to the death of M. separata. Aphicidal Activity of Osthole-Derived N-Benzoylthioureas against M. persicae.…”
Section: Data Forsupporting
confidence: 91%
“…Specifically, knock downs of AChE and EcR interfered with whitefly mating and oviposition before it resulted in mortality. The latter genes also are targets of insecticides such as Imidacloprid46 and benzoyl hydrazine4748 that affect the neuronal and steroid functions of insects. Previously RNAi technology has been shown effective in down-regulating expression of midgut-expressed osmoregulatory genes, aquaporin and alpha glucosidase of whitefly32, for which greater than 70% mortality was shown, six days post-feeding on transgenic tobacco plants, compared to negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…Control methods are based on the use of (a) insecticide treatments (bait applications (insecticides mixed with an attractant) and cover sprays); and (b) traps [20]. Organochlorides, organophosphates and carbamates were the first insecticides used against the olive fruit fly, followed by the introduction of pyrethroids, neonicotinoids, and spinosad as bait treatment, which is recognized to be an integral component of IPM as it reduces pesticide levels and environmental impact on natural enemies and pollinators [21][22][23][24][25]. Kaolin works as a physical barrier that prevents egg laying in the olive fruit [26].…”
Section: Bactrocera Oleae-psyttalia Concolor: Compatibility Between Cmentioning
confidence: 99%